Do women prefer a co-operative work environment? - Peter J. Kuhn; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2011)
Are women disproportionately attracted to work environments where cooperation rather than competition is rewarded? This paper reports the results of a real-effort experiment in which participants choose between an individual compensation scheme and a team-based payment scheme. We find that women are more likely than men to select team-based compensation in our baseline treatment, but women and men join teams with equal frequency when we add an efficiency advantage to team production. Using a simple structural discrete choice framework to reconcile these facts, we show that three elements can explain the observed patterns in the team-entry gender gap: (1) a gender gap in confidence in others (i.e. women are less pessimistic about their prospective teammates' relative ability), (2) a greater responsiveness among men to instrumental reasons for joining teams, and (3) a greater pure preference for working in a team environment among women.
urn:nbn:de:101:1-201110263363
Keywords: C91; J16; J24; J31; M5; 330; gender; cooperation; self-selection; confidence; experiment; Weibliche Arbeitskräfte; Kooperative Führung; Arbeitsgruppe; Vertrauen; Test